Comparison of the Axes and Positions of the Uterus and Vagina Between Women With and Without Pelvic Floor Organ Prolapse - Li, Song; Wen, Xuewei; Gao, Zhenhua; Ke, Kunbin; Yang, Jing; Wang, Haifeng; Mo, Yin; Zeng, Yizhen; Li, Yuan; Tian, Daoming; Shen, Jihong (Frontiers in Surgery, 2022)
Purpose To analyze the role of the axial positions of the uterus and vagina in providing pelvic floor support, encourage evaluations of pelvic floor function, and improve the understanding of the pathogenesis of pelvic organ prolapse. Methods The lengths and angles of the upper, middle, and lower axes of the vagina, uterine body, and cervix of 81 women with prolapse (prolapse group) and 57 women without prolapse (non-prolapse group) were measured and compared using magnetic resonance images. The pelvic inclination correction system (PICS) line was also compared between the groups. The coordinate parameters of the anatomical points of the uterus and vagina were measured, and their positions were analyzed. Results In the prolapse group, the uterine body-cervical angle, cervical-upper vaginal angle, uterine body-PICS line angle, cervical-PICS line angle, and lower vaginal-PICS line angle were smaller (p < 0.05) and the middle-lower vaginal angle, upper vaginal-PICS line angle, and middle vaginal-PICS line angles were larger (p < 0.05) than those in the non-prolapse group. The cervical length was longer (p < 0.05) and the middle and lower vaginal lengths were shorter (p < 0.05) in the prolapse group. The coordinate system revealed that the uterine and vaginal axes were shifted backward and downward in the prolapse group. Conclusion Patients in the prolapse group were more likely to have retroversion and retroflexion of the uterus than those in the non-prolapse group. The vagina was shortened, turned forward, and straightened, and the uterus and vagina were shifted backward and downward in the prolapse group. Changes in the axial position of the uterus and vagina are important mechanisms of pelvic floor organ prolapse.